Innovation and Creativity of Indonesian Musicians during the Covid-19 Pandemic - Putra, Rachzonja Adhy Kirana; Soewarlan, Santosa - (Gelar: Jurnal Seni Budaya, 2022)
Pandemic Covid has widespread in Indonesia since early 2020 resulting in some artistic activities paralysis. In performing arts artist are banned to make crowd, direct contact between individuals, and to travel to other cities. This causes musicians to loose opportunity to perform on the stage. To fill the void some groups of musicians find a way to make music by using digital platforms. Some of the virtual activities are: Virtual Live Music Concert, Virtual Tapping Music Concert, Drive-in Music Concert, Virtual Online Music Class, and Podjam among musicians. These have revolved in keeping the creative process among musicians in their homeland.